The impact of PT XL Axiata Tbk’s divestment on the stock zerformance of PT Mora Telematika Tbk on the Indonesia stock exchange - Seto, Agung Anggoro (International Journal of Applied Finance and Business Studies, 2026)
This research aims to examine the impact of divestment occurring in the shares of PT. Mora Telematika Tbk on the Indonesia Stock Exchange. This research is categorized as a comparative study, which aims to compare the stock performance of PT Mora Telematika Indonesia Tbk before and after the divestment by PT XL Axiata Tbk. Performance is measured using two key metrics: actual return and trading volume activity. The data used in this study are secondary data, specifically daily closing stock prices (Closed Price) sourced from published financial statements and financial performance summaries of PT Mora Telematika Indonesia Tbk. The observation period covers one month prior to the divestment and one month following the divestment by PT XL Axiata Tbk. The data analysis technique used in this research is comparative analysis, which compares stock performance based on actual return and trading volume activity of PT Mora Telematika Indonesia Tbk before and after the divestment by PT XL Axiata Tbk. The data analysis method utilizes paired sample tests, specifically the Wilcoxon test. Based on the research findings, it is concluded that the divestment had a significant impact on the actual stock returns of PT Mora Telematika Tbk. The actual returns experienced an average decline of 11%, driven by dominant factors such as negative sentiment or rumors surrounding the company’s shares, as well as investor profit-taking. On the other hand, the Trading Volume Activity (TVA) showed no significant change before and after the divestment.